Does response to percutaneous tibial nerve stimulation predict similar outcome to sacral nerve stimulation?. Issue 5 (28th April 2022) - Kapriniotis, Konstantinos; Jenks, Julie; Toia, Bogdan; Pakzad, Mahreen; Gresty, Helena; Stephens, Ross; Malde, Sachin; Sahai, Arun; Greenwell, Tamsin; Ockrim, Jeremy
Abstract: Aims: Percutaneous tibial nerve stimulation (PTNS) is a simple neuromodulation technique to treat an overactive bladder. It is unclear whether the response to PTNS would suggest a similar response to sacral nerve stimulation (SNS), and whether PTNS could be utilized as an alternative test phase for an SNS implant. This study assessed whether PTNS response was a reliable indicator for subsequent SNS trials. Methods: We performed a retrospective review of the hospital databases to collect all patients who had PTNS and who subsequently had an SNS trial in two tertiary hospitals from 2014 to 2020. Response to both interventions was assessed. A 50% reduction in overactive symptoms (frequency−volume charts) was considered a positive response. McNemar's tests using exact binomial probability calculations were used. The statistical significance level was set to 0.05. Results: Twenty‐three patients who had PTNS subsequently went on to a trial of SNS. All patients except one had previously poor response to PTNS treatment. Eight of them also failed the SNS trial. However, 15 patients (including the PTNS responder) had a successful SNS trial and proceeded with the second‐stage battery implantation. The difference in response rates between the PTNS and SNS trial was statistically significant ( p  < 0.001). Conclusions: Poor response to PTNS does not seem to predict the likelihood of patients responding to SNS. A negative PTNS trial should not preclude a trial of a sacral nerve implant. The predictive factors for good and poor responses will be the subject of a larger study.